DETERMINATION OF APPROPRIATE SPIROMETRIC INDICES IN JUVENILE GIRLS OF THE MESOMORPHIC SOMATOTYPE BASED ON MATHEMATICAL MODELING - Kyrychenko, Yu.V.; Sarafyniuk, L.A.; Androshchuk, O.V.; Khapitska, O.P.; Sarafyniuk, P.V. (World of Medicine and Biology, 2022)
Using multivariate regression analysis, which made it possible to determine the total influence of external structure indicators on the variability of spirographic body parameters, we performed mathematical modelling in girls of the mesomorphic somatotype to determine appropriate individual spirographic indices. For 12 spirometric parameters, linear regression models were built with the accuracy of character description within 55.30–96.64 %. To the greatest extent, the value of spirometric parameters was determined by the body’s girth, the pelvis’s diameters and the transverse mid-thoracic width of the distal epiphysis.